Medienkritikfähigkeit messbar machen Analyse medienbezogener Fähigkeiten bei Eltern von 10- bis 15-Jährigen (Volume 36) - Rott, Karin Julia (W. Bertelsmann Verlag, 2020)
If parents are critical and reflective about the media, they can pass this ability on to their children. But what is this ability? How can it be recorded? In her dissertation, the author developed a test procedure and collected basic data to analyze the media criticism of parents of young children. Before that, she defined the term "media criticism", placed it in the theoretical context and used it to examine her results.The study shows that the social situation influences both media education and critical media dealings. Habitualized patterns of media use are also passed on within the family.This study opens a new field of research in media education, in which the role model function of parents in dealing with media is in focus. The relevance of the topic is obvious: parents shape the media criticism of their children, i.e. the adults of tomorrow. The author uses current examples to classify the social effects of a lack of reflection and criticism in dealing with the media.